MENCEGAH DAN MENGURANGI KEKERASAN SEPAKBOLA MELALUI PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN - Sulistiyono Sulistiyono (Jurnal Pendidikan Jasmani Indonesia, 2009)
Violence is some behavior resulting ill, loss, or injury at own self or others, and the behavioral effect of violence is sacrifice existence. People who participate at football generally agree that mount painfulness and injury effect of attack at body have to specifying as violence action. Subject of Physical Education Sport and Health nearest with culture and assess in athletics can prevent and lessen athletic violence football if all instruction will lift, and attention to domain affective as one of instruction target which of vital importance to be reached. Value of fair play is a part of domain affective in student communicable Physical Education Sport and Health through various means in order to assess applicable fair play in human life in all area. When all Indonesian nation and socialize ball from player, coach, referee, audience and entirely community in football contests in Indonesia own character assess exist in teaching of fair play hence by itself step by step the violence behavior in athletics specially violence in Indonesia football can be prevented or will decrease Keywords: Football, Violence, Physical Education Sport and Health, Affective Domain, Fair Play